1974
DOI: 10.1021/ja00816a005
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of intermolecular aromatic hydrocarbon-dialkylaniline exciplexes

Abstract: The geometry of intermolecular aromatic hydrocarbon-M.V-dimethylaniline exciplexes was investigated by comparing the singlet quenching rate constants, exciplex energies, and heats of formation of the exciplexes formed upon quenching pyrene excited singlets by M/V-dimethylaniline (1) and 3,5-di-iW-butyl-/V,/V-dimethylaniline (2).The results are in accord with a sandwich-pair geometry for the 1 exciplex and a localized-pair geometry for the 2 exciplex in which the aromatic rings are adjacent but not parallel as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…S02, in heptane, K and -AH are 2550 M™1 and 11 kcal/ mol™1 5. The latter is very close to the value obtained for the complex of the same base with iodine (-AH = 12.1 kcal/mol™1).30 For this last complex, the charge transfer is obviously more pronounced, and so one can conclude that other effects such as the dipole-dipole interaction contribute to the stability of the complex.…”
supporting
confidence: 66%
“…S02, in heptane, K and -AH are 2550 M™1 and 11 kcal/ mol™1 5. The latter is very close to the value obtained for the complex of the same base with iodine (-AH = 12.1 kcal/mol™1).30 For this last complex, the charge transfer is obviously more pronounced, and so one can conclude that other effects such as the dipole-dipole interaction contribute to the stability of the complex.…”
supporting
confidence: 66%
“…The magnitude of this value is too small for a strong exciplex, and it is more likely that the slope is due to dipolar interactions. In addition, recent work by Taylor et a/. (1974) on the geometry of strong exciplexes has shown that chargetransfer is the important stabilizing force in strong exciplexes.…”
Section: Molarity C C Hmentioning
confidence: 99%
“…Furthermore, we have used a crystalline complex between PyOMe and trans -perhydroquinoline to demonstrate that the nitrogen lone-pair must adopt an orthogonal (or near orthogonal) approach to the pyrenyl basin in order for quenching to occur . Although the latter has been an integral part of the accepted quenching model for many years, it has never been demonstrated unequivocally to the best of our knowledge . Additionally, the optimal distance and angle for approach of the nitrogen lone-pair of electrons to the pyrenyl surface in the ground-state of PyOMe have been examined in detail by DFT calculations.…”
Section: Introductionmentioning
confidence: 99%